Implementation of the Safety Riding Program to Reduce Traffic Accidents in Wamena City - Nancy, Telly (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The purpose of the study was to analyze the implementation of the Safety Riding program to Reduce Traffic Accidents in Wamena City which was carried out at the Jayawijaya Police Traffic Unit. This type of research is descriptive with qualitative methods. The informants used were 12 people. The implementation of the Safety riding program in Wamena City, Jayawijaya Regency has been carried out by the agency or institution designated to implement and implement the program, but in its implementation it still needs a lot of improvement on several factors. In particular, the most dominant inhibiting factor that affects the implementation of the objectives in this program is Human Resources, both from the side of the program implementers themselves, as well as the quality of human resources from the Wamena City community as users or objectives of this Safety Riding program. Then other factors in terms of supporting facilities such as facilities and infrastructure which are still very lacking. And communication between organizations and implementing activities, this factor is also the most basic in this implementation, such as from the Satlantas and the Transportation Service sometimes there is no synchronization when implementing programs related to this program in the field. Many people in Wamena City feel that information related to Handling Traffic Safety Problems is still unclear so that many people, especially vehicle users, feel that they have been treated unfairly during the implementation of security activities related to this program on the highway.